2023
DOI: 10.1002/path.6054
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR‐induced exon skipping of β‐catenin reveals tumorigenic mutants driving distinct subtypes of liver cancer

Abstract: CRISPR/Cas9-driven cancer modeling studies are based on the disruption of tumor suppressor genes by small insertions or deletions (indels) that lead to frame-shift mutations. In addition, CRISPR/Cas9 is widely used to define the significance of cancer oncogenes and genetic dependencies in loss-of-function studies. However, how CRISPR/Cas9 influences gain-of-function oncogenic mutations is elusive. Here, we demonstrate that single guide RNA targeting exon 3 of Ctnnb1 (encoding β-catenin) results in exon skippin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Mouse liver tumors were made by Ctnnb1 exon skipping using CRISPR/Cas9 in conjunction with YAPS127A. Oncogene gain-of-function mutations in vivo under β-catenin-dependent tumorigenesis are helpful using CRISPR/Cas9 [ 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mouse liver tumors were made by Ctnnb1 exon skipping using CRISPR/Cas9 in conjunction with YAPS127A. Oncogene gain-of-function mutations in vivo under β-catenin-dependent tumorigenesis are helpful using CRISPR/Cas9 [ 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…Owing to the lack of proper antibodies, this was not confirmed [ 10 ]. Since then, more than 20 studies have identified in-frame transcripts or truncated proteins from knockout organisms generated by the CRISPR–Cas system (Table 1 ) [ 10 37 ]. One interesting study from the Farber group provided direct evidence explaining the low frequency of mutant phenotypes by reverse genetics in zebrafish.…”
Section: Evidence For Knockout Escapingmentioning
confidence: 99%
“…Functional analysis has also been conducted in mice with genes knocked out, giving similar results as in cells or zebrafish [ 27 , 29 , 37 ]; For example, different gene knockout strategies were compared for the mutant phenotypes in mice, namely a definitive-null strategy using a bacterial artificial chromosome (BAC) to remove the entire genomic sequence of the target gene, a KO-first strategy that excised exons 4–11 flanked by the loxP sites with the help of Cre recombinase, and CRISPR–Cas9-mediated knockout targeting exon 2 and 3 of the RHBDF1 gene. The phenotypes displayed by the knockout mice from the three strategies were strikingly different.…”
Section: Evidence For Knockout Escapingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the nucleus, β-catenin interacts with LEF/TCF transcription factors to regulate gene expression. Recent reports have demonstrated that similar activation of β-catenin, either via engineered deletions or CRISPR targeting of Ctnnb1 exon 3 in the liver, is sufficient to generate tumours in mice 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%